1992
DOI: 10.1139/z92-315
|View full text |Cite
|
Sign up to set email alerts
|

Viability of glochidia of two species of Anodonta exposed to low pH and selected metals

Abstract: Mature glochidia were stripped from the gills of gravid mussels and exposed to low pH (3 – 6.5), aluminum (150 – 3000 μg/L), aluminum (300 μg/L) at low pH (3–6.5), zinc (5 – 30 000 μg/L), cadmium (50–3000 μg/L), or copper (5 – 1500 μg/L) for 6 days. Viability was tested after 24, 48, 72, and 144 h by observing the ability of the glochidia to close when exposed to an irritant, 2.5 M KCl. Effective concentrations needed to reduce the closure response to 50% (EC50) under the experimental conditions were calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…Procedures for acute bioassays are better established for glochidia than juveniles, as the former have been more available for testing because they are obtained from gravid adults collected from the field rather than cultured. However, limitations with using glochidia as test organisms have become evident, with researchers reporting substantial declines in viability during laboratory studies after only short periods, ranging from hours to days, depending on the species [7,13,14]. This may be attributable to their limited energy reserves, and therefore, glochidia are only effective as test organisms for assessing acute toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Procedures for acute bioassays are better established for glochidia than juveniles, as the former have been more available for testing because they are obtained from gravid adults collected from the field rather than cultured. However, limitations with using glochidia as test organisms have become evident, with researchers reporting substantial declines in viability during laboratory studies after only short periods, ranging from hours to days, depending on the species [7,13,14]. This may be attributable to their limited energy reserves, and therefore, glochidia are only effective as test organisms for assessing acute toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Not only water temperature but also other factors such as water quality may affect the glochidial surivival rate. For example, glochidial viability of the unionoids Anodonta anatina and A. cygnea is reduced by metals such as Cu, Cd, Zn, and Al, and by low pH (Huebner and Pynnonen, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (e.g., Manley and Davenport, 1979;Kramer et al, 1989;Huebner and Pynnönen, 1992;Markich et al, 1996;Fdil et al, 2006;Schwartzmann et al, 2011) have confirmed that valve movement behavior can be used to sensitively quantify biological reactions in real-time (Figure 10) for assessing the toxicological effects of metal exposures. The observations found that upon exposure to toxic concentrations of metals, bivalves have the ability to reduce the exposure of their soft tissues for extended periods by closing their valve (Manley and Davenport, 1979;Kramer et al, 1989;Salánki and Balogh, 1989;Huebner and Pynnönen, 1992).…”
Section: Future Application Approachesmentioning
confidence: 97%
“…The observations found that upon exposure to toxic concentrations of metals, bivalves have the ability to reduce the exposure of their soft tissues for extended periods by closing their valve (Manley and Davenport, 1979;Kramer et al, 1989;Salánki and Balogh, 1989;Huebner and Pynnönen, 1992).…”
Section: Future Application Approachesmentioning
confidence: 99%